Biotechnology in animal production - Tegegne, Azage; Lahlou-Kassi, A.; Mukasa-Mugerwa, E. (Ethiopian Society of Animal Production, 1995)
There are many agroecological zones in sub-Saharan Africa but the pattern of animal production and the major problems associated with it do not generally vary. It is, therefore, appropriate to make a general assessment of the status, limitations and potential of animal production in sub-Saharan Africa in general, and Ethiopia in particular. This paper first highlights the resources, the need for improvement vis-a-vis the demand for animal products and presents the potential for improved animal production. The relevance of some of the tools to improve animal production in Ethiopia are also presented and some prerequisites for the use of biotechnology are suggested.